2019
DOI: 10.1161/res.125.suppl_1.407
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 407: Modeling Atrial Fibrillation in a Dish Using Atrial iPSC Derived Cardiomyocytes

Abstract: Mutations in multiple genes have been linked with familial atrial fibrillation (AF) but the underlying pathophysiologic mechanisms and implications for therapy remain poorly understood. To characterize the electrophysiological phenotype of an AF-linked SCN5A mutation and assess novel mechanism-based therapies, we generated patient-specific atrial induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) from a carrier with an SCN5A-E428K mutation and an unaffected family member us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hong et al [ 161 ] also developed an AF model using patient-derived iPSCs to characterize the electrophysiological properties of a known familial AF linked with an E428K mutation on SCN5A (sodium voltage-gated alpha subunit 5). Atrial iPSC-CMs with this mutation showed an increased window for the late sodium current (I Na,L ), increased beating rate, prolonged APD, and spontaneous arrhythmogenic activity.…”
Section: Deciphering Lncrna Function In Atrial Fibrillation By Hpsmentioning
confidence: 99%
“…Hong et al [ 161 ] also developed an AF model using patient-derived iPSCs to characterize the electrophysiological properties of a known familial AF linked with an E428K mutation on SCN5A (sodium voltage-gated alpha subunit 5). Atrial iPSC-CMs with this mutation showed an increased window for the late sodium current (I Na,L ), increased beating rate, prolonged APD, and spontaneous arrhythmogenic activity.…”
Section: Deciphering Lncrna Function In Atrial Fibrillation By Hpsmentioning
confidence: 99%